2008
DOI: 10.1136/gut.2007.132068
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection and the risk of Barrett's oesophagus: a community-based study

Abstract: Objective-Gastric colonization with the Helicobacter pylori bacterium is a proposed protective factor against oesophageal adenocarcinoma, but its point of action is unknown. We evaluated its associations with Barrett's oesophagus, a metaplastic change that is a probable early event in the carcinogenesis of oesophageal adenocarcinoma. Design-A case-control studySetting-The Kaiser Permanente Northern California population, a large health services delivery organization Patients-Persons with a new Barrett's oesoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(102 citation statements)
references
References 62 publications
5
94
0
3
Order By: Relevance
“…The exact mechanism by which H pylori infection affects the development of EA and esophageal SCC is still puzzling. The strongest risk factor of distal EA is Barrett's esophagus, a condition secondary to long-term gastroesophageal reflux disease, and H pylori colonization may protect against Barrett's esophagus [11,13,26] . Richwww.wjgnet.com Compared to KMUH or NTUH controls: adjusting for age (continuous), gender (female vs male), educational levels (≤ primary school vs > high school; junior and high schools vs > high school), cigarette smoking (yes vs no), alcohol consumption (yes vs no) and betel nut chewing (yes vs no); Compared to community controls: Adjusting for the above factors except for betel nut chewing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact mechanism by which H pylori infection affects the development of EA and esophageal SCC is still puzzling. The strongest risk factor of distal EA is Barrett's esophagus, a condition secondary to long-term gastroesophageal reflux disease, and H pylori colonization may protect against Barrett's esophagus [11,13,26] . Richwww.wjgnet.com Compared to KMUH or NTUH controls: adjusting for age (continuous), gender (female vs male), educational levels (≤ primary school vs > high school; junior and high schools vs > high school), cigarette smoking (yes vs no), alcohol consumption (yes vs no) and betel nut chewing (yes vs no); Compared to community controls: Adjusting for the above factors except for betel nut chewing.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, cumulative evidence has indicated that H pylori infection plays a protective role in the development of reflux esophagitis [10,11] and esophageal adenocarcinoma (EA) [6,8,12,13] . In contrast, the relationship between H pylori infection and esophageal squamous cell carcinoma (SCC) is still inconclusive [8,[14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between H.pylori and BE development seems somewhat complicated. In the literature, there are studies that reach different results on this issue; in addition to the studies reporting that the presence of H.pylori is a risk factor for BE development, there are studies reporting that it does not influence the development of BE or it prevents BE development (20)(21)(22)(23)(24)(25)(26)(27)(28)(29). In the study by Vaezi et al (29), it was found that being infected with H.pylori had a protective effect for development of BE and its malignant complications.…”
Section: Does the Presence Of Helicobacter Pylori Affect The Frequencmentioning
confidence: 99%
“…Table 5 Relationship between the level of p53 expression and grade of dysplasia weight as risk factors associated with the presence of BE [7][8][9][10][11][12][13][14][15][16] . One of the most notable findings from epidemiological reports has been a strong inverse association between H. pylori infection and dysplasia of Barrett's epithelium [17,18,[21][22][23][24][25][26] . Esophageal adenocarcinoma derived from BE is not common in Japan as compared with western countries, whereas gastric carcinoma is more prevalent in Japan.…”
Section: Variables Associated With Dysplasia In Sce-type Bementioning
confidence: 99%
“…Moreover, Helicobacter pylori (H. pylori) infection may play a key role in suppression of BE. Two main inhibiting roles for development of BE have been postulated in H. pylori infection: H. pylori-induced atrophic gastritis resulting in less gastric acid secretion; and neutralization of the gastric acid by ammonia produced by H. pylori independently of gastric atrophy [17][18][19][20][21][22][23] . Cag-A positive H. pylori infection is strongly associated with a reduced risk of esophageal adenocarcinoma, and the association is independent of gastric atrophy, suggesting the involvement of a mechanism other than reduced acidic gastric reflux [24][25][26] .…”
Section: Introductionmentioning
confidence: 99%